A study of antioxidant potential from herbal plants and the effects on Parkinson’s disease - Indri Nuraeni Pratiwi; Widhya Aligita; Marita Kaniawati (Jurnal Ilmiah Farmasi, 2021)
AbstractBackground: Parkinson's disease is the most common neurodegenerative disorder affecting more than 10 million people worldwide. This disease is characterized by progressive dopaminergic neuron damage in the substantia nigra. This damage can be triggered by aging and the presence of oxidative stress because of free radicals. Antioxidants can inhibit the formation of free radicals and reduce oxidative stress, so they can be used as an alternative treatment for Parkinson's disease.Objective: This review article aimed to provide information about the antioxidant effects of selected herbal plants on Parkinson's disease.Method: This study used literature study methods sourced from national and international scientific journals published in the last 5 years (2016-2020). Literature search were carried out using databases such as Google Scholar, PubMed®, ScienceDirect, and Garuda Portal.Results: The high content of antioxidants in plants could protect nerve cells from oxidative damage and reduce symptoms such as tremors, muscle stiffness, impaired coordination and motor balance in test animals.Conclusion: Natural antioxidants from herbal plants proved to be able to prevent oxidative stress caused by free radicals and reduce symptoms of Parkinson's disease.Keywords: Parkinson's disease, antioxidants, oxidative stress, herbal plantsIntisariLatar belakang: Penyakit Parkinson merupakan gangguan neurodegeneratif paling umum yang mempengaruhi lebih dari 10 juta orang di seluruh dunia. Penyakit ini ditandai dengan kerusakan neuron dopaminergik secara progresif di substansia nigra. Kerusakan tersebut dapat dipicu oleh penuaan dan adanya stres oksidatif akibat adanya radikal bebas. Antioksidan mampu menghambat pembentukan radikal bebas dan mengurangi stres oksidatif, sehingga dapat digunakan sebagai salah satu alternatif pengobatan penyakit Parkinson.Tujuan: Review artikel ini bertujuan untuk memberikan informasi mengenai pengaruh antioksidan dari beberapa tanaman herbal terpilih terhadap penyakit Parkinson.Metode: Penelitian ini menggunakan metode studi literatur yang bersumber dari jurnal ilmiah nasional maupun internasional yang diterbitkan 5 tahun terakhir (2016-2020). Pencarian literatur dilakukan dengan menggunakan database seperti Google Scholar, PubMed®, ScienceDirect, dan Portal Garuda.Hasil: Kandungan antioksidan yang tinggi dapat melindungi sel saraf dari kerusakan oksidatif dan mampu mengurangi gejala seperti tremor, kekakuan otot, gangguan koordinasi, dan keseimbangan motorik pada hewan uji.Kesimpulan: Antioksidan alami dari tanaman herbal terbukti mampu mencegah terjadinya stres oksidatif yang diakibatkan oleh radikal bebas dan mengurangi gejala dari penyakit Parkinson.Kata kunci : Penyakit Parkinson, antioksidan, stres oksidatif, tanaman herbal